2020
DOI: 10.3390/ijerph17238989
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Spinal Muscular Atrophy on Informal Caregivers

Abstract: Spinal muscular atrophy (SMA) is one of the most common severe hereditary diseases of infancy and early childhood. The progression of this illness causes a high degree of disability; hence, a significant burden is experienced by individuals with this disease and their families. We analyzed the time taken to care for patients suffering from SMA in European countries and the burden on their informal caregivers. We designed a cross-sectional study recording data from France, Germany, Spain and the United Kingdom.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 54 publications
3
31
1
1
Order By: Relevance
“…Therefore, our results confirm the impact of the patient's functional status on her/his CG's burden. Compared to other neuromuscular disorders (NMD), we estimated a caregiver burden comparable to Duchenne muscular dystrophy in a study cohort from Germany, UK, Italy and the US (mean ZBI score = 29/88, n = 770) [73] and a lower burden compared to spinal muscular atrophy (mean = 31.9/88, n = 68) [74].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results confirm the impact of the patient's functional status on her/his CG's burden. Compared to other neuromuscular disorders (NMD), we estimated a caregiver burden comparable to Duchenne muscular dystrophy in a study cohort from Germany, UK, Italy and the US (mean ZBI score = 29/88, n = 770) [73] and a lower burden compared to spinal muscular atrophy (mean = 31.9/88, n = 68) [74].…”
Section: Discussionmentioning
confidence: 99%
“…The publications comprised data from 14 countries, including the USA (n = 20) [48-50, 53, 54, 56, 57, 60, 63, 70, 74, 77, 80, 84-86, 88, 91-93], UK (n = 5) [52,68,81,89,98], Italy (n = 2) [59,83], Australia (n = 2) [64,71], Canada (n = 1) [75], Germany (n = 1) [55], Croatia (n = 1) [87], Korea (n = 1) [65], Japan (n = 1) [66], France (n = 1) [79], Spain (n = 4) [58,72,73,78], Sweden (n = 1) [61], Russia (n = 2) [94,97] and Turkey (n = 1) [96]. Seven studies reported multi-national data [62,67,69,76,82,90,95].…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
“…The following study designs were adopted across the 49 unique studies: retrospective analyses (n = 35) [48, 50, 53-60, 63, 65, 66, 68, 70, 72-74, 77-93], cross-sectional analysis (n = 7) [52,69,71,75,76,95,96], cost analysis (n = 2) [94,97], exploratory qualitative analysis (n = 1) [64], prospective cohort study (n = 1) [62], economic evaluation (reporting original cost data; n = 1) [61], survey (n = 1) [98] and a symposium briefing report (n =1) [67]. Because of the heterogeneity between the different types of SMA, data were Fig.…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
See 2 more Smart Citations